The challenges of metamodern and their impact on modern economic science - S. L. Sazanova (Путеводитель предпринимателя, 2020)
The article examines the current state of economic theory, provides a number of arguments that testify to its crisis. The challenges of metamodern philosophy are revealed from the point ofview of their influence on economic theory. It is established that the crisis of modern economic theory is partly due to the influence of the metamodern philosophy. Possible ways of overcoming the crisis of modern economic theory are substantiated.